2012
DOI: 10.3109/09638288.2012.672539
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in the care home: a qualitative study of the perspectives of residents with multiple sclerosis

Abstract: QoL is a broad, multidimensional construct for residents with MS. QoL measures for residents with MS should incorporate broad domains, including environmental factors. The conceptual model highlighted several areas for improving QoL of residents with MS, including more involvement of family members, encouraging independence by providing access to rehabilitation and providing support in the transition process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…Even for those discharged to longterm care facilities, it has been shown that skills learned at rehabilitation are empowering and strengthen the feeling of independence. 37,38 Future work aimed to further quantify the effect of returning home on QoL would allow a ''value-based healthcare'' 39 approach to assess effectiveness of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Even for those discharged to longterm care facilities, it has been shown that skills learned at rehabilitation are empowering and strengthen the feeling of independence. 37,38 Future work aimed to further quantify the effect of returning home on QoL would allow a ''value-based healthcare'' 39 approach to assess effectiveness of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews with persons with MS in residential care settings suggest that they may find it difficult to interact with other residents with more severe cognitive impairment. 45 This presents a unique challenge in the delivery of person-centered care that is aligned with the individual strengths, preferences, and needs of minority patient populations in residential care settings. Organizational commitment to personcentered care may not be sufficient to ensure that the social needs of persons with MS are addressed given care providers' orientation toward practice using a medical paradigm.…”
Section: The Canadian Journal Of Neurological Sciencesmentioning
confidence: 99%
“…MS seems to have a detrimental effect on the functional performance of many daily activities. The disease characteristics, the unpredictable nature of the disease, and functional disabilities experienced by people with MS seems to significantly affect their life (Riazi, Bradshaw, & Playford, 2012). Studies have also found that psychosocial factors such as lower coping, negative mood, reduced self-efficacy, and decreased perceived support effect their life and eventually lead to reduced quality of life in people with MS (Farran, Ammar, & Darwish, 2016).…”
Section: Introductionmentioning
confidence: 99%